Giant mesentery fibromatosis presenting as acute abdomen – case report - Misiak, Piotr; Piskorz, Łukasz; Wcisło, Szymon; Jabłoński, Sławomir; Brocki, Marian (Contemporary Oncology/Współczesna Onkologia, 2013)
Mesentery fibromatosis, also called abdominal desmoid, is a rare clinical entity. It is part of the clinical-pathologic spectrum of so-called deep fibromatoses. The deep fibromatoses encompass a group of benign fibroproliferative processes that are locally aggressive; they may infiltrate the adjacent organs or recur, but do not create distant metastatic lesions. The small bowel mesentery is the most common site of intraabdominal fibromatosis. However, the omentum, ileocolic mesentery, transverse or sigmoid mesocolon, or ligamentum teres may be the site of origin for intraabdominal fibromatosis. Mesenteric fibromatosis occurs in a wide age range of patients, and has no gender or race predilection. Most cases of abdominal fibromatosis occur sporadically. In this article we would like to present a case report of a patient who was admitted to the clinic due to severe abdominal pain with clinically advanced peritoneal signs. The intraoperative findings were astonishing; we found a giant desmoid which originated in the mesentery. The tumor oppressed the ileum, leading to its obstruction.